Replication of a Malaysian Strain Avian Influenza A Virus H5N1 in Madin-Darby Canine Kidney and African Green Monkey Kidney cells - Tan, Toong Seng; Sharifah Syed Hassan,; Yap, Wei Boon (Penerbit Universiti Kebangsaan Malaysia, 2016)
The use of cell lines such as Madin-Darby Canine Kidney (MDCK) and African Green Monkey Kidney (Vero) cells in influenza vaccine production is much advocated presently as a safer alternative to chicken embryonated eggs. It is thus essential to understand the influenza virus replication patterns in these cell lines prior to utilizing them in vaccine production. The infectivity of avian influenza A virus (A/Chicken/Malaysia/5858/2004) H5N1 in MDCK and Vero cell lines was first assessed by comparing the cytopathic effect (CPE) caused by the virus infection. The viral loads in both of the infected media and cells were also compared. The results showed that both of the MDCK and Vero cells began to exhibit significant CPE (p<0.05) after 48 h post-infection (h p.i). The MDCK cell line was more susceptible to the virus infection compared to Vero cell line throughout the incubation period. A higher viral load was also detected in the host cells compared to their respective culturing media. Interestingly, after reaching its maximum titer at 48 h p.i, the viral load in MDCK cells declined meanwhile the viral load in Vero cells increased gradually and peaked at 120 h p.i. Overall, both cell lines support efficient H5N1 virus replication. While the peak viral loads measured in the two cell lines did not differ much, a more rapid replication was observed in the infected MDCK samples. The finding showed that MDCK cell line might serve as a more time-saving and cost-effective cell culture-based system compared to Vero cell line for influenza vaccine production.